Digital Learning Design Innovation: Evaluating Behavioral Intention to Use Microlearning in Child Protection Professional Training in Indonesia - Safira Ryanatami; Elfindah Princes (CV. Creative Tugu Pena, 2026)
The high prevalence of child protection cases necessitates continuous professional learning; however, conventional training models often lead to training fatigue due to time constraints, heavy workloads, and the demanding nature of frontline responsibilities. This study aims to evaluate learners’ acceptance of microlearning-based e-learning as an instructional design innovation for professional training in child protection in Indonesia. Guided by the Technology Acceptance Model (TAM), the study examines the influence of Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) on Behavioral Intention (BI). A quantitative approach was employed involving 136 respondents from cross-sectoral professional backgrounds within child protection ecosystems, selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that the proposed model demonstrates strong predictive power (R² = 0.661). PEOU shows a strong positive effect on PU, and both PEOU and PU significantly influence BI. Notably, PEOU contributes more substantially than PU in shaping learners’ intention to adopt the platform. These findings indicate that system usability, intuitive interaction, and flexibility of learning access are critical determinants of adoption among professional learners. Furthermore, ease of use is found to support the reduction of cognitive load, enabling learners to focus more effectively on complex and sensitive child protection materials. The study concludes that the success of digital learning innovations in professional contexts depends not only on perceived instructional benefits but also on the ergonomic quality of user experience (UX) that accommodates professionals’ work rhythms and learning needs